If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n = 4n + -36 Reorder the terms: n = -36 + 4n Solving n = -36 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. n + -4n = -36 + 4n + -4n Combine like terms: n + -4n = -3n -3n = -36 + 4n + -4n Combine like terms: 4n + -4n = 0 -3n = -36 + 0 -3n = -36 Divide each side by '-3'. n = 12 Simplifying n = 12
| 36x/4=-81 | | m-19=-13 | | 3x-15=-60 | | -1y+4=x | | (15/3y)-(6/2y-2) | | 3x-15/4=-15 | | 3=-2x+18 | | 4x+54=10 | | 4x/3-3=-7 | | 11xx8/47=4x | | 7x+4-3x=-14+2+8 | | 4(x+10)+2(-x+4)=10 | | 6u-1=3 | | 5(x+6)-3(x+2)=6 | | 5(x+10)=3(x-10) | | 4(3x-28)=5(x+21) | | 3p+4=5 | | 6x-75/4=3x | | 2x+12=-5+12 | | 6(4.5+1)=33 | | 6(q+1)=33 | | 4p-8=2p+4 | | 8n-12=6 | | 6m-5=2m+19 | | 3(x-1)+8=4 | | 15x+2=25+4x | | 73x/3x=11 | | 10x+5=120+4x | | 5y-(y+3)=3x-1 | | 1.2=2.16-1.2y | | 5(3x-4)=2(6-2x) | | 5-2x+7(x-3)=20-2(x+10) |